2022
DOI: 10.1155/2022/1054299
|View full text |Cite|
|
Sign up to set email alerts
|

Botulinum Toxin Type A Injection Improves the Intraperitoneal High Pressure in Rats Treated with Abdominal Wall Plasty

Abstract: The aim of the study is mainly to study the subject of BoNT-A injection to improve IAH in rats undergoing abdominal angioplasty. The study problem in surgery, especially in ICU, burn, and trauma centers, intra-abdominal hypertension (IAH), and abdominal compartment syndrome (ACS) are common complications. At present, there are various treatments for IAH. The intramuscular injection of Botulinum toxin type A (BoNT-A) into the abdominal wall has received a lot of attention. Based on this, this study proposes a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Computational Intelligence and Neuroscience has retracted the article titled "Botulinum Toxin Type A Injection Improves the Intraperitoneal High Pressure in Rats Treated with Abdominal Wall Plasty" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computational Intelligence and Neuroscience has retracted the article titled "Botulinum Toxin Type A Injection Improves the Intraperitoneal High Pressure in Rats Treated with Abdominal Wall Plasty" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%
“…Computational Intelligence and Neuroscience has retracted the article titled “Botulinum Toxin Type A Injection Improves the Intraperitoneal High Pressure in Rats Treated with Abdominal Wall Plasty” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%